Metaphors in the Pandemic Language of the Polish Episcopate - Jankosz, Magdalena; Przyczyna, Wiesław (Name – style – text: A jubilee book dedicated to Professor Elżebieta Umińska-Tytoń, 2023)
The aim of the article is to show the language of the Polish Episcopate used in its letters and messages regarding the COVID-19 pandemic from its beginning until August 2021. The research problem was to inquire about the role of metaphors used. The research material consisted of documents published on the website of the Polish Bishops’ Conference. The first part of the paper describes the phenomenon of metaphorisation in relation to disease, the second presents the types of metaphors used by the bishops, the third one presents the nature of these metaphors, while the fourth one describes the role they played.